Diary of a survivor: nineteen years in a Cuban women's prison - Rodríguez Aguilera, Ana (St. Martin's Pr., 1995)
"A personal account of life in prison by an early opponent of the Castro regime. Written as a testimonial and memoir, it documents the sordid abuses visited upon female prisoners in Castro's jails. One of the very few accounts of its kind, it is part of a genre that probes resistance to dictatorship. Offers details of how Castro's propaganda machine attempts to turn opponents of communism into outcasts"--Handbook of Latin American Studies, v. 57